2012
DOI: 10.1179/1743284710y.0000000010
|View full text |Cite
|
Sign up to set email alerts
|

Hardness and tensile strength study on Al356–B4C composites

Abstract: Additions of high modulus particles to aluminium alloys offer the potential to develop a lightweight composite with high strength and hardness. Al356 matrix composites reinforced with B4C particles were prepared using stir casting method. Hardness and tensile strength of unreinforced alloy and composites with different volume percentages of boron carbide particles were measured and compared. Microstructural characterisation revealed an almost uniform distribution of the B4C particles in the matrix. It also sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Boron carbide is an attractive ceramic reinforcement for a range of application including wear components, mechanical seals, aerospace parts, and cutting tools because of its high impact and wear resistance, low density, high melting point, and excellent resistance to chemical agents as well as high capability for neutron absorption. Further, its density (2.52 g/cm 3 ) is very close to that of Al alloy matrix [9,12].…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…Boron carbide is an attractive ceramic reinforcement for a range of application including wear components, mechanical seals, aerospace parts, and cutting tools because of its high impact and wear resistance, low density, high melting point, and excellent resistance to chemical agents as well as high capability for neutron absorption. Further, its density (2.52 g/cm 3 ) is very close to that of Al alloy matrix [9,12].…”
Section: Introductionmentioning
confidence: 62%
“…Iron may be present either as iron or as iron oxide. It is reported that iron might get oxidized during this process and oxide layers, in particular Fe 2 O 3 layers generated during wear, act as solid lubricants and help to reduce the wear rates [3,[28][29][30]. It is noted that the debris of the composites with coating are associated with the formation of more iron-rich layers on the contact surfaces.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies on alloy A356 reinforced with B 4 C and Al 2 O 3 particles showed that ceramic particle addition enhanced hardness and tensile strength of the materials. 15,16 This improvements on mechanical properties are interpreted as grain refinements due to the addition of hard ceramic particles. 16 The reinforcement with B 4 C particles of wrought aluminium alloys such as 7075, 6061 showed also similar results.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, depending on the overall effect of all the factors involved, the behavior of the composite form change will be different. This non-conformance stress also depends on the temperature at which the composite cools [15][16][17]. It should be borne in mind that although the thermal inconsistency stress will increase the strength, this increase is not very high in composite particles.…”
Section: Introductionmentioning
confidence: 99%